Construction Site Safety Helmet Detection In Mobile Application - Ang, Suzanne (2023)
The construction industry has had exceptionally high accident rates compared to other industries. However, most of these injuries and accidents can be avoided if workers wore appropriate personal protective equipment (PPE) like helmets, vests, boots, or safety glasses. The absence of PPE has been identified as a significant issue affecting construction site safety in several research studies. Each piece of equipment in a set of PPE plays a vital role in minimizing the risk of injuries. Therefore, onsite workers must take into consideration this precaution when working in dangerous environments. It is impossible for employers to keep an eye on their workers 24/7 that are most of the time located in remote areas. To overcome this limitation, the use of computer vision-assisted technology is becoming increasingly common. Therefore, this project is aimed at developing an application which focuses on construction site safety helmet detection using computer vision-based technology. The application receives alerts on helmet non-compliance on workers detected using the technology and sends the alerts to the employer for further actions to be taken.